Atherogenic ω-6 Lipids Modulate PPAR- EGR-1 Crosstalk in Vascular Cells - Jia Fei; Carla Cook; Miriah Gillespie; Bangning Yu; Khyra Fullen; Nalini Santanam (PPAR Research)
Atherogenic ω-6 lipids are physiological ligands of peroxisome proliferator-activated receptors (PPARs) and elicit pro- and antiatherogenic responses in vascular cells. The objective of this study was to investigate if ω-6 lipids modulated the early growth response-1 (Egr-1)/PPAR crosstalk thereby altering vascular function. Rat aortic smooth muscle cells (RASMCs) were exposed to ω-6 lipids, linoleic acid (LA), or its oxidized form, 13-HPODE (OxLA) in the presence or absence of a PPARα antagonist (MK886) or PPARγ antagonist (GW9662) or PPAR-specific siRNA. Our results demonstrate that ω-6 lipids, induced Egr-1 and monocyte chemotactic protein-1 (MCP-1) mRNA and protein levels at the acute phase (1–4 hrs) when PPARα was downregulated and at subacute phase (4–12 hrs) by modulating PPARγ, thus resulting in altered monocyte adhesion to RASMCs. We provide novel insights into the mechanism of action of ω-6 lipids on Egr-1/PPAR interactions in vascular cells and their potential in altering vascular function.